Chitin Nanofibers Retain the Postharvest Quality and Shelf Life of Papaya (Carica papaya L.) - Hossain, Md Shaheen; Kabir, Md Yamin; Shams, Md Iftekhar; Khan, Shamim Ahmed Kamal Uddin; Sultana, Afrin (Journal of the Bangladesh Agricultural University, 2025)
Papaya is a nutrient-dense fruit, but due to its climacteric nature, its shelf life is short. The effect of chitin nanofiber (CNF) on the physico-chemical changes, microbial characteristics, and shelf life of papaya cv. Shahi was examined in an experiment conducted during the period from January 29th to February 14th, 2024, at the Germplasm Centre, Horticulture Laboratory, and Plant Pathology Laboratory of the Agrotechnology Discipline, Khulna University, Khulna. The experiment was replicated three times and included five treatments: control, 0.1% chitin nanofiber (CNF), 0.2% CNF, 0.3% CNF, and 0.4% CNF. Total soluble solids (TSS) and weight loss are two physicochemical measures that rise with storage in both treated and untreated fruits. The incidence and severity of the disease showed a rising trend. The amount of vitamin C, however, dropped. The lowest amount of total soluble solids (8.30%) was found in the 0.1% chitin nanofiber treatment. The least amount of weight was lost (11.56%) was found with the 0.2% chitin nanofiber treatment. The 0.3% chitin nanofiber treatment had the lowest disease severity (45.77%) on the ninth day of storage, while the control had the highest disease severity (53.96%). Papaya's shelf life varies greatly depending on the CNF concentrations. The 0.4% CNF had the longest shelf life (10.17 days), whereas the control had the shortest shelf life (6.31 days). Overall, papaya's shelf life and other postharvest quality attributes were better preserved at 0.4% CNF. J Bangladesh Agril Univ 23(4): 532–541, 2025